2016
DOI: 10.1155/2016/7802957
|View full text |Cite
|
Sign up to set email alerts
|

The Pattern of Juvenile Idiopathic Arthritis in a Single Tertiary Center in Saudi Arabia

Abstract: Introduction. Juvenile Idiopathic Arthritis (JIA) is the most common chronic arthritis in children. Our aim is to describe demographic, clinical, and laboratory characteristics and treatment of JIA patients followed up in Pediatric Rheumatology clinic in a tertiary center in Saudi Arabia. Methods. Medical records of all patients who are followed up between January 2007 and January 2015 were retrospectively reviewed. Data were collected about demographic, clinical, and laboratory features and treatment. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
15
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 32 publications
6
15
1
Order By: Relevance
“…While Uveitis was manifested among (6.3%) of cases of oligoarticular and polyarticular subtypes. This was close to Ozdogan et al 21 , El-Hemiari et al 22 21 reported lower results (12%, 5%) respectively. The higher percentage of positive ANA results could be attributed to higher incidence of infections inducing the illness.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…While Uveitis was manifested among (6.3%) of cases of oligoarticular and polyarticular subtypes. This was close to Ozdogan et al 21 , El-Hemiari et al 22 21 reported lower results (12%, 5%) respectively. The higher percentage of positive ANA results could be attributed to higher incidence of infections inducing the illness.…”
Section: Discussionsupporting
confidence: 88%
“…15,20 On contrary, to many studies the numbers of male patients were higher than the females. [11][12][13][14][15][16] However, our results matched Ozdogan et al 21 and El-hemiari et al 22 who reported male predominance.…”
Section: Discussionsupporting
confidence: 87%
“…Unlike similar studies published in Oman and Tunisia where Polyarticular JIA is the most common subtype 46.7%, 66% respectively (11,12) , whereas systemic juvenile arthritis (36.5%) was the most common subtype in another study from Saudi Arabia (13) . Table 6 summarizes the published data on JIA patterns in different countries.…”
Section: Discussioncontrasting
confidence: 67%
“…However, it provided information on the rarity of JIA in general, then on SF-JIA in our African context. Other studies on this subject had made the same observation [26]. In western countries, it is the oligoarticular form which predominate and SF-JIA represented 5 up to 15% of JIA [27] [28] [29].…”
Section: At the Socio-demographic Levelmentioning
confidence: 58%